THE The relationship of organizational culture and training to the driver performance in PT Blue Bird Group Tbk - Yohana Natalena; Christina Natalia (Universitas Kristen Indonesia, 2018)
Abstract Human Resources (HR) pitself is a very important determinant for the effectiveness of running activities within the organization. Organization is a place where people gather, cooperate rationally and systematically, in utilizing organizational resources efficiently and effectively to achieve predetermined goals. In achieving for goal to still have the value of organizational culture within its members, in addition to organizational culture, training is also one way to develop the human resource capabilities of an organization. The success of organizational culture and training provided in to hope to improve the quality of human resources available. The purpose of this research is to know the relationship of organizational culture and training with the performance of the driver of PT Blue Bird Group Tbk. This research is descriptive-quantitative that is by taking a sample of 75 people and data were analyzed using correlation analysis by Rank Sperman. The result of the research shows that (1) There is a significant correlation between training with driver performance of PT Blue Bird Group Tbk with Rank Sperman correlation. (2) There is a significant correlation between organizational culture with driver performance of PT Blue Bird Group Tbk with Rank Sperman correlation . Keywords: culture, training to the driver performance.